2017
DOI: 10.1038/sc.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in comprehensive management of spinal cord injury in India and in the Asian Spinal Cord network region: findings of a survey of experts, patients and consumers

Abstract: Our study brought out that SCI in India and ASCoN region face numerous challenges that affect access to almost all aspects of comprehensive management of SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Outof-pocket healthcare expenditure in a poverty-ridden society like Nigeria may endanger the entire population. Moreover, SCI patients and their families are at risk of poverty and in dire need of inancial assistance [9]. Another important risk factor for UTI observed in this study is the practice of entrusting the purchase of consumables and medical supplies in the hands of patients' relations.…”
Section: Discussionmentioning
confidence: 80%
“…Outof-pocket healthcare expenditure in a poverty-ridden society like Nigeria may endanger the entire population. Moreover, SCI patients and their families are at risk of poverty and in dire need of inancial assistance [9]. Another important risk factor for UTI observed in this study is the practice of entrusting the purchase of consumables and medical supplies in the hands of patients' relations.…”
Section: Discussionmentioning
confidence: 80%
“…However, these facilities are often inaccessible and unaffordable for many patients. A recent study reported that nearly 63% of Indian patients with SCI reached a definitive centre after two to three institutional transfers and 22% of the patients reached a definitive centre more than a month after the injury [16]. The magic window of 24 h is often lost when trying to get the patient to an equipped centre for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This case was managed in a center recognised by the government as the Apex Tertiary Level Center for management of spinal injuries. However, the same facilities and expertise is not available in most other centers in the country [20], and thus most of the centers would not have been able to manage such a patient with the same kind of positive outcome. India does not have appropriate public health resources with only 3.93% of the GDP spent on health expenditure [21].…”
Section: Indian Scenariomentioning
confidence: 99%
“…However, 66% of the population still lives in rural areas [22], where health needs are mainly taken care by the public hospitals (primary health centers), which have only basic amenities and such patients could not have been appropriately managed. In fact, most of such centers would not have the multi-disciplinary team required for the management of such patients [20].…”
Section: Indian Scenariomentioning
confidence: 99%